Mechanical performance of rattan cane wood fiber–reinforced polymer at high temperatures - Cornelius Ogbodo Anayo Agbo (Academia Materials Science)
The growing applications of natural fibers and green composites in manufacturing various products have expanded the search for more functional and sustainable fibers. Due to availability, cost, and environmental concerns, there is a continued effort to seek more natural fibers that can effectively substitute synthetic ones. The high resilience quality observed in cane wood sticks spurred interest in their potential for fiber production and use in composites. However, one drawback of using natural fiber in composites is its poor temperature tolerance. This article seeks to study the thermal behavior of rattan cane wood fiber–reinforced plastic under elevated temperatures. The high-temperature analysis was conducted by heating the produced cane wood fiber/polyester composite sample from 50°C to 400°C and taking weight measurements at 50°C intervals. At 200°C, the composite began degrading, with evidence of a 4% mass reduction. A further increase to 250°C resulted in a mass reduction of 9.1%. Additionally, a mass reduction of 10.5% was observed when the temperature was increased to 300°C. Subsequently, as the temperature was increased to 350°C and 400°C, mass reductions of 31.6% and 67.6%, respectively, were observed. The structural integrity of the material was also compromised, as evidenced by the presence of cracks, charring, and loss of strength. This implies that the composite is thermally unstable at such high temperatures.